DAMPAK BULLYING TERHADAP KEPRIBADIAN DAN PENDIDIKAN SEORANG ANAK - Siti Nur Elisa Lusiana Lusiana; Siful Arifin (Institut Kariman Wirayudha Sumenep, 2022)
The Purpose of this study was to analyze the impact of bullying on children’s personalities. The research approach in this study uses a qualitative research type. The data collection method is in the form of analysis which is literature study and documentation. The data analysis technique used descriptive-qualitative.The results showed that bullying was an aggressive act, both repeatedly, and there were differences in strength between the perpetrator and the victim. The impact of bullying for perpetrators and victims, including bullying perpetrators, has minimal empathy in social interactions. It is not only empathy that is problematic but also abnormal behavior. Hyperactive and pro-social behavior are related to the bullying’s actions against the environment around them. Bullies have a higher level of mental health problems, especially emotional symptoms, compared to victims ofbullying. The impact on victims of bullying such as experiencing physical and verbal abuse. Actions like this can be a prolonged trauma for the victim. Not only the trauma experienced by the victims of bullying,academic learning outcomes are also greatly affected by the victims of bullying. Physical violence received by victims of bullying includes often being socially isolated, having no close friends, not having good relationships with parents, decreased mental health,and worst of all, bullying can lead to depression that can lead to suicide. Efforts to overcome bullying in children, the main thing is to provide love, trust, and involve both the perpetrator and the victim. Not only that,cooperation between schools, teachers, and parents is needed to overcome bullying against children.